PET/CT in Radiotherapy Planning for Head and Neck Cancer - Newbold, Katie; Powell, Ceri (Frontiers in Oncology, 2012)
The use of PET/CT as an adjunct in radiotherapy planning is an attractive option in head and neck cancer (HNC) for several reasons. First, with potentially better identification of the disease extent i.e. staging, the risk of geographical miss of radiation delivery to the gross tumour volume (GTV) is reduced. Second, in characterising the biological behaviour of the disease for example, areas of hypoxia, rich or poor vascularity or high cell proliferation, PET/CT can identify biological target volumes (BTVs) either for escalation of radiation dose or to predict the requirement for the addition of a radiosensitiser or alternative treatment strategies. 18F-FDG is the most common tracer used in oncology studies, but many other tracers have been investigated with several entering clinical practice, although these remain predominantly in the research domain in HNC. These issues will be discussed in this review.